Heparin-induced Thrombocytopenia – Pathogenesis and Treatment - Greinacher, A. (Thrombosis and Haemostasis, 1999)
Heparin-induced thrombocytopenia (HIT) is now recognized as the most frequent immune-mediated adverse drug reaction. During the last decade, fundamental aspects of the pathogenesis of HIT have been resolved. The understanding of some the mechanisms underlying the development of new, paradox thromboembolic complications in HIT led to the concept that thrombin generation plays a key-role in clinically manifest HIT. Consequently new therapeutic concepts imply the use of drugs with either indirect of direct anti-thrombin activity such as donaparoid-sodium and the recombinant hirudin lepirudin. During the last years results of first prospective studies assessing various treatment regimens in HIT became available. Although data of randomized trials are still missing some treatment recommendations can already be drawn from these studies. This review summarizes key aspects of the pathogenesis of HIT and provides an overview of current treatment strategies.
Keywords: Danaparoid; hirudin; heparin; platelets; low-molecular weight heparin